A Fault Handling Process for Faults in District Heating Customer Installations - Sara Månsson; Marcus Thern; Per-Olof Johansson Kallioniemi; Kerstin Sernhed (Energies, 2021)
Faults in district heating (DH) customer installations cause high return temperatures, which have a negative impact on both current and future district heating systems. Thus, there is a need to detect and correct these faults soon after they occur to minimize their impact on the system. This paper, therefore, suggests a fault handling process for the detection and elimination of faults in DH customer installations. The fault handling process is based on customer data analysis since many faults manifest in customer data. The fault handling process was based on an analysis of the results from the previous fault handling studies, as well as conducting a workshop with experts from the DH industry. During the workshop, different organizational and technical challenges related to fault handling were discussed. The results include a presentation of how the utilities are currently working with fault handling. The results also present an analysis of different organizational aspects that would have to be improved to succeed in fault handling. The paper also includes a suggestion for how a fault handling process based on fault detection using data analysis may be designed. This process may be implemented by utilities in both current and future DH systems that interested in working more actively with faults in their customer installations.